Diagnosis of competencies in the meetings industry in Poland, Hungary and Ireland in post-COVID-19 period - Bartłomiej Walas (LLC "CPC "Business Perspectives", 2021)
The freezing of economies due to the COVID-19 pandemic caused damage not only on the sales side but also on the labor market due to the outflow of staff from companies specializing in the organization of meetings. The return of the meetings industry sector to the development path will involve skillful change management, including in the area of competencies and skills. To inventory and assess the competencies of employees in the meetings industry, this study was carried out among specialized enterprises in the meetings industry in Poland, Hungary, and Ireland, on samples of two research groups, i.e. the Director General (CEO) and operational employees based on questionnaires and individual in-depth interviews (IDI). The obtained results allowed to establish the hierarchy of self-assessment of own managerial competencies, assessment of the competencies of the CEO by the employees, areas of increasing team competencies, and areas of staff development in the sector shortly, contributing to the recovery from the pandemic crisis. Raising the competencies and qualifications of employees is perceived as one of the most powerful tools for overcoming the pandemic crisis, obtaining 68% positive indications among CEOs in Poland, 77% indications in Hungary, and 84% in Ireland. In all analyzed countries, the meetings industry is indicated as a strategic product of the tourist market. Among the planned long-term actions aimed at overcoming the pandemic crisis, increasing employee competencies is perceived as an opportunity for the companies operating the meetings industry sector (90% in Poland, and 80% in Hungary and Ireland). AcknowledgmentThis study was done in frames of the project “Vocational competences in MICE sector” co-financed in frames of European Union program Erasmus + as part of the program The Dialog for Transformation, Erasmus+, 2020–2021.